ChemInform Abstract: Maleimide‐Modified Gold Nanoparticles (AuNPs): A Versatile Platform for Interfacial Click Reactions Leading to Chemically Modified AuNPs. Issue 43 (7th October 2016) - Gobbo, Pierangelo; Workentin, Mark S.
Abstract: Review: [30 refs.